1988
DOI: 10.1002/bsl.2370060208
|View full text |Cite
|
Sign up to set email alerts
|

Combining cognitive‐behavioral therapy and pharmacotherapy in the treatment of pedophilic incest offenders

Abstract: Treatment programs for incest offenders traditionally do not differentiate between pedophilic and nonpedophilic perpetrators. This oversight has failed to meet the specialized needs of pedophilic incest offenders, who differ from other incest as well as nonfamilial sex offenders in important ways. This paper describes a treatment intervention combining cognitive‐behavioral therapy and pharmacotherapy for the specialized treatment needs of the pedophilic incest offender. A case report is presented to illustrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…The pedophilia explanation received the most support. The present data support the findings of others who have stressed the importance of sexual deviance (Abel et al, 1981; Frude, 1982; Menard & Johnson, 1992; Stermac & Hucker, 1988). Although not as sexually deviant as extrafamilial offenders, the intrafamilial offenders were clearly sexually deviant as a group.…”
Section: Discussionsupporting
confidence: 92%
“…The pedophilia explanation received the most support. The present data support the findings of others who have stressed the importance of sexual deviance (Abel et al, 1981; Frude, 1982; Menard & Johnson, 1992; Stermac & Hucker, 1988). Although not as sexually deviant as extrafamilial offenders, the intrafamilial offenders were clearly sexually deviant as a group.…”
Section: Discussionsupporting
confidence: 92%
“…There is some evidence to suggest that a multidisciplinary approach to treatment, consisting of both medication management and empirically supported CBT approaches, may be the most effective strategy for the management of high-risk sexual offenders. A number of authors have cited the importance of using pharmacological treatments as an adjunct to psychological interventions (Briken & Kafka, 2007; Harrison, 2010; Lösel & Schmucker, 2005; Raymond et al, 2001; Saleh & Berlin, 2003; Schober et al, 2005; Stermac & Hucker, 1988). Namely, professionals working with sexual offenders have reported that sex drive reducing medications have helped limit the influence of deviant sexual thoughts or fantasies.…”
Section: La As An Adjunct To Psychotherapymentioning
confidence: 99%